Prospective Determination of Orbital Perfusion Dominance before Intra-Arterial Chemotherapy for Retinoblastoma Using Time-of-Flight Magnetic Resonance Angiography - Monroe, Eric J.; Otjen, Jeffrey P.; Wright, Jason N.; Perez, Francisco A.; Chick, Jeffrey Forris Beecham; Hallam, Danial K.; Ferguson, Mark R. (Journal of Clinical Interventional Radiology ISVIR, 2022)
Intra-arterial chemotherapy (IAC) represents a mainstay in the treatment of retinoblastoma. In a minority of cases, the external carotid artery (ECA) serves as the dominant supply to the central retinal artery and is associated with prolonged fluoroscopy times and higher intraprocedural radiation doses. The aim of this study was to evaluate the utility of time-of-flight (TOF) magnetic resonance angiography (MRA) for prospective determination of internal (ICA) versus ECA dominance for procedural planning. Between April 2017 and December 2020 (44 months), staging MR prior to IAC for retinoblastoma included variant spatial saturation band position TOF angiography. Exams were then retrospectively reviewed for concordance of ICA versus ECA dominance between the two modalities. Eight consecutive patients were included in the study. Mean patient age at time of diagnosis was 20.3 ± 10.7 months (range: 2.7–33.2 months). Ten affected eyes were included (2 cases of bilateral disease), with stage D disease in eight eyes and stage B disease in two eyes. MRA techniques demonstrated antegrade ophthalmic artery (OA) flow in 9/10 (90%) of affected eyes. Subsequent catheter angiography confirmed ICA dominant supply in 9/9 (100%). For a single affected eye (10%), the OA was demonstrated as orthotopic by T2 flow void, nonvisualized on anterior saturation TOF sequences, and faintly visualized on posterior saturation TOF sequences. Aggregate MRA to catheter angiographic concordance was 10/10 (100%). Variant saturation TOF MRA predicts ICA versus ECA dominant supply to the central retinal artery in retinoblastoma.
Keywords: retinoblastoma; oncology; intra-arterial chemotherapy; angiography; magnetic resonance